Motor truck engine tune up & electronics manual (New York, N.Y.: Motor, 1988)
"This engine tune up and electronics manual covers service specifications and procedures on 1984-89 models available at the time of its publication. This manual is divided into four sections using three tabs."
English text.
Description based on: 2nd ed.
SERBIB/SERLOC merged record
Keywords: Trucks -- Motors -- Maintenance and repair -- Handbooks, manuals, etc; Trucks -- Electronic equipment -- Maintenance and repair -- Handbooks, manuals, etc; Trucks -- Pollution control devices -- Maintenance and repair -- Handbooks, manuals, etc; Trucks -- Electronic equipment -- Maintenance and repair; Trucks -- Motors -- Maintenance and repair; Trucks -- Pollution control devices -- Maintenance and repair; Handbooks and manuals; Handbooks and manuals